INDIGENIST MOBILIZATION: ‘IDENTITY’ VERSUS ‘CLASS’ AFTER THE KERALA MODEL OF DEVELOPMENT? - Luisa Steur (Central European University, Department of Sociology and Social Anthropology, 2011)
This thesis analyses the recent rise of "adivasi" (indigenous/tribal) identity politics in the South Indian state of Kerala. It discusses the complex historical baggage and the political risks attached to the notion of "indigeneity" in Kerala and poses the question why despite its draw- backs, a notion of indigenous belonging came to replace the discourse of class as the primary framework through which adivasi workers now struggle for their rights. The thesis answers this question through an analysis of two inter-linked processes: firstly, the cyclical social movement dynamics of increasing disillusionment with - and distantiation from - the class-based platforms that led earlier struggles for emancipation but could not, once in government, structurally alter existing relations of power. And secondly, the political-economic processes associated with "neoliberalism" that changed the everyday working lives of subaltern groups in Kerala in such as way as to make them more amenable to indigenism than to the older forms of "class-based" mobilization. Through an analysis of these processes, this thesis makes a critical contribution to the wider debate on the causes and meanings of the global rise of indigenous identity politics at this juncture in the capitalist world system.